Die Evaluering Van Verpleging In Suid-Afrika - H. Steenberg (AOSIS, 1978)
In any institution there must be a system of evaluation but it is important to remember that evaluation will be useless unless it follows careful planning. Planning gives direction for action. The planning process includes formulation of an objective towards which purposeful action, to the best of nursing ability, will be directed. Whenever a specific nursing procedure is decided on, provision must at the planning stage be made for continuous testing of the effectivity of the procedure in terms of predetermined objectives which the specific procedure is required to reach. These objectives will serve as the established criteria for evaluation.